L’Océanie, métaphore de l’ailleurs et territoire de mythes chez Le Clézio et Jean-Luc Coatalem - István Cseppentö (Viatica, 2019)
Through the key notion of myth, this article studies two authors who lived in Oceania: Jean-Luc Coatalem and J. M. G Le Clézio. While experiencing a nostalgia for childhood, as well as setting out on a personal quest conditioned in part by the painter Gauguin, Coatalem develops a reflection on the changeable nature of the Tahitian myth in Je suis dans les mers du Sud. In his essay Raga, approche du continent invisible, Le Clézio insists on the protection of threatened peoples, the dichotomy between dream and reality and the harmful effects of civilization in Oceania.